Analisis Kemampuan Penyelesaian Masalah Matematis Pada Materi Sistem Persamaan Linear Dua Variabel Siswa SMP - karlina, iis (Prosiding Sesiomadika, 2023)
Iis Karlina1, Lessa Roesdiana2 Universitas Singaperbangsa Karawang email: 2010631050134@student.unsika.ac.id1, lessa.roesdiana@fkip.unsika.ac.id2 The ability to think at a high level is indicated by the student’s ability to solve problems that have more than one answer or way of solving. This study aims to determine the ability of junior high school students to solve problems in the material of the two-variable linear equation system (SPLDV). Because the material of the two-variable linear equation system (SPLDV) is one of the Because the materials of the two-variable linear equation system (SPLDV) is one of the materials that is still widely confused by students. This research is a quantitative research of descriptive methods. The population in this study was 23 grade IX students of SMP Negeri 2 Klari for the 2022/2023 School Year. Sample selection obtained IX-D students as an experimental class. The instrument used in this study was a test instrument.The data collection technique carried out is the presentation of a description question test. The data analysis techniques used are (1) making assumptions, (2) making mathematical manipulations, (3) drawing conclusions, and providing arguments against the correctness of the solution, (4) observe the correctness of the argument.